2015
DOI: 10.1063/1.4935829
|View full text |Cite
|
Sign up to set email alerts
|

Note: A novel technique for analysis of aqueous solutions by laser-induced breakdown spectroscopy

Abstract: Surface-enhanced Raman spectroscopy (SERS) substrates typically consist of gold or silver nanoparticles deposited on a non-conductive substrate. In Raman spectroscopy, the nanoparticles produce an enhancement of the electromagnetic field which, in turn, leads to greater electronic excitation of molecules in the local environment. Here, we show that these same surfaces can be used to enhance the signal-to-noise ratio obtained in laser-induced breakdown spectroscopy of aqueous solutions. In this case, the SERS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…), the achieved magnitude of signal enhancement is reasonable for a routine LIBS instrument, and is also similar to values reported in other NELIBS studies for Ag NPs (e.g. [ 2,7]). Please also note that 3.) that show a monotonous decrease as a function of both variables.…”
Section: Signal Enhancement On Ag/ito Substratessupporting
confidence: 89%
See 2 more Smart Citations
“…), the achieved magnitude of signal enhancement is reasonable for a routine LIBS instrument, and is also similar to values reported in other NELIBS studies for Ag NPs (e.g. [ 2,7]). Please also note that 3.) that show a monotonous decrease as a function of both variables.…”
Section: Signal Enhancement On Ag/ito Substratessupporting
confidence: 89%
“…ms), only smaller signal enhancement factors can be attained [3,5] and that the enhancement also depends on the excitation potential of the electronic transition of the element studied [2][3][4]. It was also demonstrated that the NELIBS analysis of liquid samples is also possible, if they are dried onto substrates formerly prepared by NP deposition [4,6,7] or by NP embedding [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…for enhancing the signal of analytes deposited on top of the NP layer, rather than that of substrates below them, as in the examples discussed so far. This is for example the case of the analysis of micro-drops of liquid solutions [24,25]. As it is well-known, solutions can be successfully analyzed with LIBS either directly in the liquid phase by Double Pulse (DP) techniques or by depositing and drying drops of solution on a substrate.…”
Section: Nelibs Of Liquid Solutionsmentioning
confidence: 99%
“…First, the nanoparticles may increase the number density of particles of the sample in the ablation process 39 . Second, the nanoparticles may decrease the ablation threshold 40 . NELIBS can allow trace chemicals in fruit and vegetables to be detected at concentrations that cannot be detected using the ordinary LIBS method.…”
Section: Resultsmentioning
confidence: 99%